Development of Real-Time Polymerase Chain Reaction Assays for the Detection and Differentiation of Infectious Bursal Disease Virus Subtypes - Kong, Lih Ling (2009)
Two different real-time polymerase chain reaction (PCR) detection approaches based on SYBR Green I dye and Taqman probe based assays were developed for the detection and differentiation of infectious bursal disease virus (IBDV) subtypes. Both approaches were able to detect and differentiate IBDV subtypes based on the use of subtype-specific primers or subtype-specific probes where the primers were designed based on single nucleotide polymorphism (SNP) concept. After optimization of the primer combinations and PCR parameters, very virulent-specific primer, IF & IVIR, and classical-specific primer, IF & RCLA were used in the SYBR Green I real-time RT-PCR assay. Plasmid DNA carrying the VP4 gene of the references IBDV strains: very virulent strain UPM94/273 and classical strain D78 were established and used as positive controls in the real time RT-PCR. The developed assay had a dynamic detection limit which spans over 5 log10 concentration range for very virulent and spans over 7 log10 concentration range for classical strain, respectively. The correlation coefficient for amplification of very virulent and classical strain was R2 = 0.9918 and R2 = 0.9977, respectively. No amplification was found when the subtype-specific primers were used to amplify other avian RNA viruses. The performance of the SYBR Green I based assay was tested on various IBDV isolates including 10 previously characterized IBDV and 11 commercial vaccine strains. The very virulent-specific primer only detected and amplified the very virulent IBDV with threshold cycle (CT) ranged from 14.93 to 21.52 and melting temperature (Tm) between 85.6°C to 88.0°C. The classical-specific primer was only able to amplify the classical IBDV with CT value ranged from 11.99 to 20.89 and Tm between 85.6°C to 86.8°C. The diagnostic efficacy of the developed assay was also evaluated using bursal samples obtained from experimentally infected chickens. Bursal samples collected from D78 vaccine infected chickens at day 3 and 5 p.i were positive for IBDV with average CT of 23.05+1.31, Tm of 85.8+0.17°C and average CT 21.82+1.42, Tm of 86.0+0.28°C , respectively. Bursal samples collected at day 10 p.i from this group were also found positive for IBDV with average CT of 24.42+1.20 and Tm of 85.9+0.18°C. On the other hand, only bursal samples collected at day 3 and 5 p.i were found positive for yery virulent IBDV with average CT 19.39+0.72, Tm of 86.6+0.14°C and average CT 23.55+1.39, Tm of 86.5+0.19°C, respectively. In the case of samples from dual infection with different IBDV subtypes, viral RNA was detectable only on day 3 and 5 p.i. In general, majority of the bursal samples have higher very virulent virus with an average CT value ranged from 21.24+0.68 to 22.19+0.97 compared to vaccine virus with Ct value ranged from 23.88+0.74 to 25.36+1.19. The performance of the developed SYBR Green I based assay was analyzed with other standard diagnostic methods. In the uninfected control group, no obvious microscopic lesions were found in the bursa and the lesions score was less than 1.0. However, mild bursal lesions without signs of inflammation with lesions score less than 3.0 was detected from bursal tissue obtained from chickens inoculated with vaccine strain D78. Based on the lesion score, it was clear that bursal pathology developed rapidly, with complete loss of tissue architecture by day 3 p.i. when the chickens were infected with virulent IBDV. The correlation between ELISA antibody titers and real-time CT values were inversely related, where the lower titers of antibodies associated with higher level of viral RNA as found in chickens infected with very virulent strain UPM94/273. On the other hand, vaccine strain D78 induced higher detectable antibody titers than UPM94/273, which indirectly support less virus replication with late positive amplification in real-time RT-PCR. Thus, the level of viral RNA in bursal samples obtained from D78 infected chickens was lower than UPM94/273 infected chickens. A total of 37 bursal samples from IBD suspected field cases were collected and then tested on the developed assay. The developed SYBR Green I based PCR assay was able to detect 9 samples positive for very virulent, 4 positive for classical IBDV and 12 samples positive for both very virulent and vaccine strains of IBDV. Sequence analysis of the hypervariable region of the VP2 gene of the IBDV samples revealed that the residues involved in determining the virulence of VV IBDV and CL IBDV were highly conserved. For the Taqman based duplex real-time PCR assay development, a new set of primers FWDC and RVSC were designed from the conserved region of VP4 of both very virulent and classical strains. A dual-labeled fluorescent probe each specific for very virulent IBDV (ProVV) and vaccine IBDV (ProCL) were designed The performance of the developed Taqman assay was compared with other PCR methods namely conventional RT-PCR and previously developed SYBR Green I assay. The Taqman assay was found far more superior in terms of turn around time and sensitivity. With the aid of β-actin gene, the Taqman assay was also used to determine the viral load fold changes in bursal samples that were positive for both vaccine and very virulent IBDV. Majority of these samples have higher viral load fold change in very virulent than the classical strain except for three samples MB078/04, MB001/05 and MB033/05 which showed higher fold change in classical strain than very virulent strain. In conclusion, this study has successfully developed SYBR Green I based and Taqman based one-step real-time PCR assays for rapid detection and differentiation of IBDV subtypes in particular very virulent and classical IBDV strains.